The impact of chronic stress on intracellular redox balance: A systems level analysis. Issue 7 (5th April 2023) - Geddie, Hannah; Cairns, Megan; Smith, Logan; van Wyk, Minette; Beselaar, Leandrie; Truter, Nina; Rautenbach, Fanie; Marnewick, Jeanine L.; Joseph, Danzil E.; Essop, M. Faadiel
Abstract: Chronic psychosocial stress is implicated in the onset and progression of noncommunicable diseases, and mechanisms underlying this relationship include alterations to the intracellular redox state. However, such changes are often investigated in isolation, with few studies adopting a system level approach. Here, male Wistar rats were exposed to 9.5 weeks of chronic unpredictable mild stress and redox status assays were subsequently performed on cardiac, hepatic, and brain tissues versus matched controls. The stressed rats displayed an anxious phenotype, with lowered plasma corticosterone levels ( p  = 0.04 vs. Controls) and higher plasma epinephrine concentrations ( p  = 0.03 vs. Controls). Our findings showed organ‐specific redox profiles, with stressed rats displaying increased myocardial lipid peroxidation ( p  = 0.04 vs. Controls) in the presence of elevated nonenzymatic antioxidant capacity ( p  = 0.04 vs. Controls). Conversely, hepatic tissues of stressed rats exhibited lowered nonenzymatic antioxidant capacity ( p  < 0.001 vs. Controls) together with increased superoxide dismutase (SOD) activity ( p  = 0.05 vs. Controls). The brain displayed region‐specific antioxidant perturbations, with increased SOD activity ( p  = 0.01 vs. Controls) in the prefrontal cortex of the stressed rats. These findings reveal distinct stress‐related organ‐specific vulnerability to redox perturbations and may provide novel insights into putative therapeutic targets. Abstract : Chronic psychosocial stress is implicated in the onset and progression of non‐communicable diseases, and mechanisms underlying this relationship include alterations to the intracellular redox state. Here, male Wistar rats were exposed to 9.5 weeks of chronic unpredictable mild stress and redox status assays were subsequently performed on cardiac, hepatic and brain tissues versus matched controls. Our findings reveal distinct stress‐related organ‐specific vulnerability to redox perturbations and may provide novel insights into putative therapeutic targets.